Step-by-step explanation:
2- 7x + 34 - 6-(766)
2-7x + 34 - 6 - 766
2 - 7x - 738
-7x - 736
-(7x + 736
I think the best value for x is -9 because 6 x -9 = 54, minus 8 equals -44.
Answer:
I think it's A
Step-by-step explanation:
Answer:
![(AB)^T = B^T.A^T (Proved)](https://tex.z-dn.net/?f=%28AB%29%5ET%20%3D%20B%5ET.A%5ET%20%20%28Proved%29)
Step-by-step explanation:
Given (AB )^T= B^T. A^T;
To prove this expression, we need to apply multiplication law, power law and division law of indices respectively, as shown below.
![(AB)^T = B^T.A^T\\\\Start, from \ Right \ hand \ side\\\\B^T.A^T = \frac{B^T.A^T}{A^T}.\frac{B^T.A^T}{B^T} (multiply \ through) \\\\ = \frac{A^{2T}.B^{2T}}{A^T.B^T} \\\\=\frac{(AB)^{2T}}{(AB)^T} \ \ (factor \ out \ the power)\\\\= (AB)^{2T-T} \ (apply \ division \ law \ of \ indices; \ \frac{x^a}{x^b} = x^{a-b})\\\\= (AB)^T \ (Proved)](https://tex.z-dn.net/?f=%28AB%29%5ET%20%3D%20B%5ET.A%5ET%5C%5C%5C%5CStart%2C%20from%20%5C%20Right%20%5C%20hand%20%5C%20side%5C%5C%5C%5CB%5ET.A%5ET%20%3D%20%5Cfrac%7BB%5ET.A%5ET%7D%7BA%5ET%7D.%5Cfrac%7BB%5ET.A%5ET%7D%7BB%5ET%7D%20%28multiply%20%5C%20through%29%20%5C%5C%5C%5C%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%3D%20%5Cfrac%7BA%5E%7B2T%7D.B%5E%7B2T%7D%7D%7BA%5ET.B%5ET%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B%28AB%29%5E%7B2T%7D%7D%7B%28AB%29%5ET%7D%20%5C%20%5C%20%28factor%20%5C%20out%20%5C%20the%20power%29%5C%5C%5C%5C%3D%20%28AB%29%5E%7B2T-T%7D%20%20%5C%20%28apply%20%5C%20division%20%5C%20law%20%5C%20of%20%5C%20indices%3B%20%5C%20%5Cfrac%7Bx%5Ea%7D%7Bx%5Eb%7D%20%3D%20x%5E%7Ba-b%7D%29%5C%5C%5C%5C%3D%20%28AB%29%5ET%20%5C%20%28Proved%29)